PENERAPAN EVIDENCE BASED NURSING POSISI LATERAL 30 DERAJAT DAN MASSAGE EVOO (EXTRACT VIRGIN OLIVE OIL) TERHADAP PENCEGAHAN LUKA TEKAN PADA PASIEN DI RUANG ICU - Anasya Firmansyah, (2023)
The Intensive Care Unit (ICU) is a component of a hospital with specialized staff and facilities. Patients with critical conditions will experience a decrease in consciousness and immobilization which requires the patient to be bed rest, prolonged bed rest can cause pressure sores. Pressure sores are damage to the layers of the skin or soft tissue due to long-term pressure. Pressure sores can occur in the sacrum, heel, ischium, greater trochanter, malleolus (lateral to medial), and occiput caused by prolonged pressure, friction between the body and the mattress surface, and other factors. Pressure sores can be prevented by giving a lateral position of 30o every 2 hours and Massage EVOO (Extract Virgin Olive Oil). The purpose of this study was to determine the effectiveness of the combined application of 30o lateral position and EVOO Massage (Extract Virgin Olive Oil) in patients in the ICU. This study uses the Braden scale assessment to measure the risk of pressure sores. The results of the study were obtained after implementing the combination intervention for 4 days, no pressure sores occurred, the skin became moist, and hydrated after the 9th day of treatment in the ICU.